Complementary Optimization of Hydropower with Pumped Hydro Storage–Photovoltaic Plant for All-Day Peak Electricity Demand in Malawi - Evance Chaima; Jijian Lian; Chao Ma; Yusheng Zhang; Sheila Kavwenje (Energies, 2021)
Solar energy is currently dispatched ahead of other renewable energy sources. For the first time, this study presents a concept of exploiting temporary–periodical runoff discharge in the Shire River. Pumped hydro storage–photovoltaic plant (PHS–PV) was optimized to satisfy the all-day peak electricity demand in Malawi. The effect of varying the net head on the PHS system in both the generation and pumping operation modes was investigated. The bi-objective optimization evaluated the system reliability for day-time and night-time operation together with implied costs of investment for the whole system. The optimized system generated above 53% of added power as contrasted to single-source power generation from the existing hydropower plants. The estimated optimal capacities were 182 MWp (solar PV) and 86 MW (PHS plant). These additional optimal capacities achieved a 99.8% maximum system reliability (Loss of Power Supply Probability—LPSP—of 0.2%) and Levelized Cost of Energy—LCOE—of 0.13 USD/kWh. The overall investment cost of the PHS–PV system was estimated at 671.23 USD for an LPSP of 0.20%. The net head varies from 15.5 to 17.8 m with an impact on electricity generation of the PHS–PV system. More notably, the PHS–PV production matches with daily day-time and night-time peak loads and functions as a peaking plant.